Situating implementation science (IS) in res(IS)tance: a conceptual frame toward the integration of scholarship from the black radical tradition - Cory D. Bradley; Whitney C. Irie; Elvin H. Geng (Frontiers Media S.A., 2024)
This manuscript undertakes a disciplinary self-critique of the field of implementation science, a field which attempts to bridge the gap between evidence-based interventions and their practical application. Despite the heightened emphasis on health equity and racial disparities, the field's current discourse is limited by key epistemic shortcomings. First, even though prevalence of implementation gaps between racialized groups in the United States necessitates a comprehensive understanding of the systems perpetuating these disparities, the field does not operate with a general explanation for disparities not as a failure of systems, but a system historically and structural designed to produce disparities. Second, the field has attempted to address disparities without adequate dialog with a broad tradition of anti-racist and anti-colonial sociology, history and epistemology, and therefore risks a decontextualized analysis of disparities and under-informed approaches to achieving equity. Fortunately, scholarship from the Black radical tradition (BRT), such as the Public Health Critical Race Praxis (PHCRP), Critical Race Theory (CRT), and more broadly conceptual frameworks from post-modern, anti-colonial, Black feminist studies and social epistemology can offer to implementation science frameworks that center power dynamics and racialized oppression. This epistemic re-alignment of implementation research to "center at the margins" can enable the field of implementation science to more critically examine and dismantle systems that perpetuate racial inequalities in access to and utilization of health interventions. For example, normalization and dynamic fit, which are thought to be key mechanisms of implementation, are revealed in the light of this tradition of scholarship to be potentially problematic acquiescence to oppressive systems. Drawing from the concept of resistance anchored in the scholarship of the Black radical tradition as well as contemporary social epistemology such as the work of José Medina and Maria Fricker about epistemic justice, the authors further advance that implementation science could make more substantial contributions to the dismantling of racialized systems and actively work toward health justice through the transdisciplinary lens of resistance. This is a call to action for integrating implementation science with critical philosophical and theoretical perspectives rooted in Black studies and related insights, which have been acquired through the struggle for social justice, to inform the design of implementation strategies and research projects that improve health services and health outcomes for health disparity populations.